ACCOMODATION STRATEGY IN BUYING AND SELLING CONVERSATIONS AT GANG BARU TRADITIONAL MARKET CHINATOWN SEMARANG - Kepirianto, Catur; Poedjosoedarmo, Soepomo; Suhandano, Suhandano (Faculty of Humanities, Diponegoro University, 2019)
Language is a means of communication to convey idea, mind, and feeling to the other. The research problems are the accommodation in buying and selling conversation between buyers and sellers in Gang Baru traditional market Chinatown Semarang and the accommodation direction. This research applies descriptive qualitative method. To collect data, it applies observation, tapping, and recording. Then the data are analyzed descriptively based on the theory of accommodation. The findings show that there is an accomodation in the conversation between buyers and sellers in traditional market Chinatown Semarang. The direction of accommodation are both convergence and divergence. In the convergence, the speakers adapt positively, otherwise in the divergence, the speakers adapt negatively. The interpersonal interaction provides the speech in a conversation. Each talk or speech has its own function and becomes the component to arrange the comprehensive relation in a conversation. There are functions on convergence and divergence accommodation. The convergence accommodation has functions to maintain the symmetric speech, to reactualize the solidarity, to keep cooperative speech, to reduce interpersonal difference, to consider the other view, and to provide adaptation. While the divergence accommodation has functions to bargain, to retain the argument, to keep personal speech, to maintain the identity, to keep personal identity, to maintain ethnic identity, to retain the distance, to keep asymmetric speech, and to maintain idiosyncratic speech. It is implied that the speech accommodation in Gang Baru traditional market Chinatown Semarang represents such markers as solidarity, cooperative, symmetric, asymmetric, tolerant, identity, and ethnic markers.